Percepção de idosos muito idosos sobre a dor na realização das atividades diárias - Barbara Pires de Andrade Lage Cabral (2017)
Population aging is a phenomenon that happens all over the world. In Brazil, the group that grows the most corresponds to the age group of 80 years and more, called the oldest old. With the increasing proportion of elderly people, there is an increase in noncommunicable diseases, which causes pain and can lead to a process of functional disability. Pain is a subjective experience and refers to an existential feat, in which the person suffers in his totality and his reaction is mediated by the culture, the individuals life history and his relationship with what surrounds him. The aim of this study was to understand the perception of oldest old people regarding pain. The specific objectives were: to discuss the elements that participate in the construction of meanings of the pain among the oldest old; to understand how the oldest old people with pain perceives the way of performing daily activities; and to identify the strategies used during the activities of daily living. This is a qualitative study based on the anthropological reference, with individuals aged 80 years and older that participated in the multicenter, international, longitudinal study Back Complaints in the Elderly (BACE). The data collection was performed by semi-structured interview. The number of participants was defined by saturation criterion and the data were analyzed using the thematic content analysis technique. After a careful analysis of the interviewees, three categories emerged: "The constant experience of pain", "Understanding the pain" and "Accomplishing activities in the daily life with pain". Thirty women and two men aged from 80 to 91 years old participated in the study. Participants reported frequent pain, related pain to aging, disability and loneliness, and despite theirs constant pain, they still were independent to perform basic activities of daily living. As for instrumental activities of daily living, they reported to do it intermittently throughout the day and to ask theirs family and friends for help. Involvement in advanced activities of daily living was considered a way to relieve the pain. Through these results it was possible to listen to the elderly with pain and, since pain is subjective, to understand the way in which they relate to it and what makes them remain independent and engaged in theirs activities even though they still feel strong and constantly pain.